Bridging structures and values: integrating Social Network Analysis and Value Creation to study learning networks - Nijs, Jelle; van Diepen, Rianne; de Groot, Esther; Thoonen, Bart (Proceedings of the International Conference on Networked Learning, 2026)
Learning increasingly occurs within networks that span formal, informal, online and offline contexts. To understand how such networks support learning, both their structural features and the value they generate must be examined. This round table explores how quantitative or structure-oriented methods such as Social Network Analysis and qualitative or experience-based evaluation frameworks can be integrated to study networked learning more comprehensively. Participants will exchange experiences with analyzing learning in networks, discuss methodological approaches, and identify examples that link network structures to perceived value for learning. Through group dialogue and synthesis, the session aims to outline preliminary principles for an integrated conceptual model and develop methodological recommendations for future research on learning networks.